The Rise and Impact of COVID-19 in India - Kumar, S. Udhaya; Kumar, D. Thirumal; Christopher, B. Prabhu; Doss, C. George Priya (Frontiers in Medicine, 2020)
The coronavirus disease (COVID-19) pandemic, which originated in the city of Wuhan, China, has quickly spread to various countries, with many cases having been reported worldwide. As of May 8, 2020, in India, 56,342 positive cases were reported. India, with a population of more than 1.34 billion and the second largest population in the world, will have difficulty in controlling the transmission of severe acute respiratory syndrome coronavirus 2among its population. Multiple strategies would be highly necessary to handle the current outbreak; those include computational modeling, statistical tools, and quantitative analyses to control the spread as well as to rapidly develop a new treatment. The Ministry of Health and Family Welfare of India has created awareness about the recent outbreak and has taken necessary actions to control the spread of COVID-19. The central and state governments are taking several measures and formulating several wartime protocols to achieve this goal. Moreover, the Indian government implemented a 55-day lockdown throughout the country that started on March 25, 2020, to reduce the transmission of the virus. This outbreak is inextricably linked to the economy of the nation, as it has dramatically impeded industrial sectors because people worldwide are currently cautious about engaging in business in the affected regions.